The evolving role of social media in enhancing quality of life: a global perspective across 10 countries - Marzo, Roy Rillera; Jun Chen, Hana W.; Ahmad, Absar; Thew, Hui Zhu; Choy, Ja Shen; Ng, Chee Han; Chew, Chen Loong Alyx; Heidler, Petra; King, Isabel; Shrestha, Rajeev; Rahman, Farzana; Rana, Jehan Akhter; et al. (BioMed Central, 2024)
Background: Excessive or inappropriate use of social media has been linked to disruptions in regular work, well-being, mental health, and overall reduction of quality of life. However, a limited number of studies documenting the impact of social media on health-related quality of life (HRQoL) are available globally. Aim: This study aimed to explore the perceived social media needs and their impact on the quality of life among the adult population of various selected countries. Methodology: A cross-sectional, quantitative design and analytical study utilized an online survey disseminated from November to December 2021. Results: A total of 6689 respondents from ten countries participated in the study. The largest number of respondents was from Malaysia (23.9%), followed by Bangladesh (15.5%), Georgia (14.8%), and Turkey (12.2%). The prevalence of social media users was over 90% in Austria, Georgia, Myanmar, Nigeria, and the Philippines. The majority of social media users were from the 18–24 age group. Multiple regression analysis showed that higher education level was positively correlated with all four domains of WHOQoL. In addition, the psychological health domain of quality of life was positively associated in all countries. Predictors among Social Media Needs, Affective Needs (β = -0.07), and Social Integrative Needs (β = 0.09) were significantly associated with psychological health. Conclusion: The study illuminates the positive correlation between higher education levels and improved life quality among social media users, highlighting an opportunity for policymakers to craft education-focused initiatives that enhance well-being. The findings call for strategic interventions to safeguard the mental health of the global social media populace, particularly those at educational and health disadvantages.